Patterns of in vitro behaviour characterizing cells of spontaneously metastasizing K2M rat sarcoma - Veselý, P; Chaloupková, A; Urbanec, P; Urbancová, H; Bohác, L; Krchnáková, E; Franc, F; Sprincl, L; Vousden, K; Moss, R (Folia biologica, 1987)
Cells of K2M rat sarcoma and their descendants (RP, RPS) form tumours in syngeneic inbred rat strain LEW/CUB. Thirty to fifty per cent of tumour-bearing rats develop metastases, preferentially in the lung. In vitro, a quasi-stellate dynamic morphotype was characteristic of K2M cells and their descendants (RP, RPS): a highly changeable round or spindle-shaped or multipolar rather thick cell body with two or more protrusions of various length, often branching, and broadened at the tips, where vivid membrane activity was observed. Changeability of appearance and directionality of locomotion were stimulated in medium of pH 6.5. The enhanced expression of this morphotype correlated with the increased metastatic potential. In vitro, in poor, slightly acid medium metastasizing cells preserved the quasi-stellate dynamic morphotype and survived longer than non-metastasizing cells. It is likely that the observed combination of traits, viz. the quasi-stellate dynamic morphotype and, under unfavourable conditions, prolonged survival, increased migratory activity and decreased mitotic rate could be of significance in the metastatic cascade, mainly for the escape from the primary site.
Keywords: metastázy nádorů; DNA, Neoplasm; Cell Line; Microscopy, Electron, Scanning; Rats; Cell Movement; Actins; Cytoskeleton; transfekce; mikroskopie elektronová rastrovací; aktiny; Mice; cytoskelet; krysa rodu Rattus; experimentální sarkom; Neoplasm Metastasis; zvířata; pohyb buněk; DNA nádorová; Transfection; potkani inbrední LEW; myši; Sarcoma, Experimental; Rats, Inbred Lew; buněčné linie; Animals